Recent Progress in Daytime Radiative Cooling: Is It the Air Conditioner of the Future? - Santamouris, Mattheos; Feng, Jie (Buildings (Basel), 2018)
Radiative cooling is a well-researched area. For many years, surfaces relying on radiative cooling failed to exhibit a sub-ambient surface temperature under the sun because of the limited reflectance in the solar spectrum and the reduced absorptivity in the atmospheric window. The recent impressive developments in photonic nanoscience permitted to produce photonic structures exhibiting surface temperatures much below the ambient temperature. This paper aims to present and analyze the main recent achievements concerning daytime radiative cooling technologies. While the conventional radiative systems are briefly presented, the emphasis is given on the various photonic radiative structures and mainly the planar thin film radiators, metamaterials, 2 and 3D photonic structures, polymeric photonic technologies, and passive radiators under the form of a paint. The composition of each structure, as well as its experimental or simulated thermal performance, is reported in detail. The main limitations and constraints of the photonic radiative systems, the proposed technological solutions, and the prospects are presented and discussed.